2021
DOI: 10.1039/d1ay01637g
|View full text |Cite
|
Sign up to set email alerts
|

Mercury ion-engineering Au plasmonics on MoS2 layers for absorption-shifted optical sensors

Abstract: Mercury ions can modulate the surface engineering effect of MoS2. Based on the cooperative optical characteristics of semiconducting MoS2 and plasmonic gold nanostructures, a novel colorimetric mercury sensing is established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Therefore, additive MoS 2 nanosheets served as seeds, and consequently, the growth of Au nanostructures in the presence of MoS 2 seeds was proposed. Our previous studies indicated that the growth of Au nanostructures on heterostructural MoS 2 substrates was influenced by a series of coexisting metal ions and biomolecules, such as mercury ions and thiol compounds. , From the absorption spectra, it was found that with the addition of 0.4 μM l -cysteine, the peak wavelengths of the CTAB-Au + solution and MoS 2 reaction products declined from 656 nm to 606 nm. When the l -cysteine concentrations increased from 0.4 to 1.6 μM, remarkable red shifts of wavelengths were observed from the absorption spectra and a series of colorful products dispersed in aqueous solution were noticed (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, additive MoS 2 nanosheets served as seeds, and consequently, the growth of Au nanostructures in the presence of MoS 2 seeds was proposed. Our previous studies indicated that the growth of Au nanostructures on heterostructural MoS 2 substrates was influenced by a series of coexisting metal ions and biomolecules, such as mercury ions and thiol compounds. , From the absorption spectra, it was found that with the addition of 0.4 μM l -cysteine, the peak wavelengths of the CTAB-Au + solution and MoS 2 reaction products declined from 656 nm to 606 nm. When the l -cysteine concentrations increased from 0.4 to 1.6 μM, remarkable red shifts of wavelengths were observed from the absorption spectra and a series of colorful products dispersed in aqueous solution were noticed (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…Although a few studies on the chiral growth on Au seeds were remarkably conducted, ,, studies on the construction of chiral nanostructures on heterogeneous seeds are rarely reported and the heterogeneous seeds for the extensional growth might cause the morphological and characteristic diversity of hybrid chiral nanostructures. In our previous studies, we found that the ascorbic acid-reduced Au ions and the heterostructural Au nanoplasmonics were formed on the ultrasonic-exfoliated MoS 2 nanosheets . The reactions between HAuCl 4 and MoS 2 contribute to the appearance of the nanostructures, which possess diverse morphologies and exhibit unexpected optical properties.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, gold NPs are unstable in complex systems, resulting in emerging difficulties in practical analysis and testing. [10][11][12] In case of nonspecific aggregation, gold NPs are normally prepared in the presence of stabilizers, such as small molecules, 13 proteins, 14 nucleic acids, 15,16 polymers, 17 and inorganic materials, 18,19 and LSPR performances promote a broad range of applications. [20][21][22] Nevertheless, even though gold NPs can be stabilized by chemical ligands, slight changes in colorimetric signals are still recorded when nanoprobes are added in these complex samples.…”
Section: Introductionmentioning
confidence: 99%
“…Recently nano-plasmonic effects have proven to be an effective means for enhancing photocurrent generation [ 7 ] or absorption for sensing [ 8 ], tunable antennae [ 9 ], and tuning the wavelength of absorption and emission [ 10 ]. Metal nanoparticles hybridized with 2D materials or graphene can modulate the absorption of the quantized states [ 11 , 12 ] in these materials, leading to coherence effects due to light-matter interaction.…”
Section: Introductionmentioning
confidence: 99%